2022
DOI: 10.1089/heq.2022.0034
|View full text |Cite
|
Sign up to set email alerts
|

Unified in Our Diversity to Address Health Disparities Among Asian Americans, Native Hawaiians, and Pacific Islanders

Abstract: The COVID-19 pandemic disproportionately impacted Asian Americans, Native Hawaiians, and Pacific Islanders (AA/NHPIs) in the United States. AA/NHPIs have historically been subjected to discrimination, which was exacerbated by the pandemic. To bring attention to their unique concerns, an AA/NHPI Interest Group of the National Institutes of Health Community Engagement Alliance Against COVID-19 Disparities (CEAL) was formed. This article highlights major concerns raised by the Interest Group: The pervasive and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Previous studies have found perceived financial stress to be associated with cost-related treatment nonadherence behavior trends in NHPI populations [18]. Other studies note cultural safety, an intention to learn about diverse cultures, consideration of historical contexts of different ethnic groups, and emphasizing cautious communication with NHPI patients when introducing treatment regimens [19]. Insight into direct opinions concerning treatments will further illuminate both concerns and barriers to considering aducanumab.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have found perceived financial stress to be associated with cost-related treatment nonadherence behavior trends in NHPI populations [18]. Other studies note cultural safety, an intention to learn about diverse cultures, consideration of historical contexts of different ethnic groups, and emphasizing cautious communication with NHPI patients when introducing treatment regimens [19]. Insight into direct opinions concerning treatments will further illuminate both concerns and barriers to considering aducanumab.…”
Section: Discussionmentioning
confidence: 96%
“…The speculative mechanism behind this disparity may reside in the widened socioeconomic status gap between these two racial groups. NHPI individuals have long been identified as a racial group that has disproportionate adverse health outcomes and limited access to health resources in Hawaii [ 11 ]. These disparities were similarly reflected in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This further illustrates the disparities between socioeconomic statuses and healthcare outcomes. Native Hawaiian and Pacific Islander (NHPI) populations are of particular interest because of their significant presence in Hawaii and the observation that they have been historically linked to disproportionate healthcare disparities [ 11 ]. Because each TBI has a unique etiology, pathophysiology, and numerous confounding variables, such as the patient’s current health, a generalized recommendation for efficacious recovery is not yet well-defined [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Native Hawaiians and Pacific Islanders (NHPI) and Asians are understudied minorities [1][2][3]. NHPI suffer heightened risks of hypertension, diabetes, and stroke (and experience strokes at younger ages), have shorter average lifespans, and live in poorer socioeconomic conditions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%